The WheelCams on the IDEFIX rover - Naomi Murdoch; Valérian Lalucaa; Cecily Sunday; Simon Tardivel; Jean Bertrand; Nicolas Théret; Damien Vivet; Alice Amsili; Colas Robin; Panos Delton; Alexia Duchene; Quentin Douaglin; et al. (Progress in Earth and Planetary Science)
Abstract IDEFIX, the Martian Moons eXploration (MMX) mission Phobos rover, will be the first of its kind to attempt wheeled-locomotion on a low-gravity surface. The IDEFIX WheelCams, two cameras placed on the underside of the rover looking at the rover wheels, provide a unique opportunity to study the surface properties of Phobos, regolith behaviour on small-bodies and rover mobility in low-gravity. The information gained about Phobos’ surface will be of high importance to the landing and sampling operations of the main MMX spacecraft, in addition to being valuable for understanding the surface processes and geological history of Phobos. Here we introduce the WheelCam science objectives, the instrument and the characterisation activities. We also discuss the on-going preparations linked to the analysis and interpretation of the WheelCam images on the surface of Phobos.